Cognitive functions and mental performance of team sports athletes - P. Chaynikov; V. Cherkasova; A. Kulesh (National Electronic Information Consortium (NEICON), 2020)
Objective: to study cognitive functions and mental performance of team sports athletes' and persons who are not involved in sports. Materials and methods: The study has 141 participants (23,2 ± 1,7 years), 76 female (23,4 ± 1,8 years) and 64 male (23,0 ± 1,6 years). Group of team sports athletes (main group) consisted of 61 participants: 31 male (22,3 ± 1,3 years), 30 female (23,1 ± 2,1 years). Control group consisted of persons who were not involved in sports, and included 80 people, (23,6 ± 1.5 years):men - 34 (23,7 ± 1,5 years), women - 46 (23,6 ± 1,5 years). Diagnostics of mental health included psychophysical tests focused on memory, attention and mental productivity assessment. Results: athletes have demonstrated higher level of visual memory, volume and switching of attention, mental productivity and mental performance in comparison with persons who were not involved in sports. Male athletes had higher rates of visual memory, volume and switching attention, mental performance in comparison with men who were not involved in sports. Female athletes and women who are not involved in sports have similar level of aural, visual memory, attention but mental productivity and mental capacity are higher in the group of female athletes. Male athletes had higher level of volume and switching of attention, mental productivity and mental performance in comparison to female athletes. Men and women who are not involved in sports differ only in terms of visual memory upwards at women side. Conclusions: high rates of cognitive functions of athletes comparing with persons who are not involved in sports confirm positive impact physical activities on central nervous system. Findings may be used as baseline data for testing cognitive functions and mental performance of athletes in different time segments of sports activity.